A synthetic enzymatic pathway for extremely thermophilic acetone production based on the unexpectedly thermostable acetoacetate decarboxylase from Clostridium acetobutylicum. Issue 12 (23rd October 2018) - Zeldes, Benjamin M.; Straub, Christopher T.; Otten, Jonathan K.; Adams, Michael W. W.; Kelly, Robert M.
Abstract: One potential advantage of an extremely thermophilic metabolic engineering host ( T opt ≥ 70°C) is facilitated recovery of volatile chemicals from the vapor phase of an active fermenting culture. This process would reduce purification costs and concomitantly alleviate toxicity to the cells by continuously removing solvent fermentation products such as acetone or ethanol, a process we are calling "bio‐reactive distillation." Although extremely thermophilic heterologous metabolic pathways can be inspired by existing mesophilic versions, they require thermostable homologs of the constituent enzymes if they are to be utilized in extremely thermophilic bacteria or archaea. Production of acetone from acetyl‐CoA and acetate in the mesophilic bacterium Clostridium acetobutylicum utilizes three enzymes: thiolase, acetoacetyl‐CoA: acetate CoA transferase (CtfAB), and acetoacetate decarboxylase (Adc). Previously reported biocatalytic pathways for acetone production were demonstrated only as high as 55°C. Here, we demonstrate a synthetic enzymatic pathway for acetone production that functions up to at least 70°C in vitro, made possible by the unusual thermostability of Adc from the mesophile C. acetobutylicum, and heteromultimeric acetoacetyl‐CoA:acetate CoA‐transferase (CtfAB) complexes from Thermosipho melanesiensis and Caldanaerobacter subterraneus, composed of a highly thermostable α‐subunit and a thermally labile β‐subunit. The three enzymes produce acetone in vitro at temperatures of at least 70°C, paving the way for bio‐reactive distillation of acetone using a metabolically engineered extreme thermophile as a production host. Abstract : One potential advantage of an extremely thermophilic metabolic engineering host ( T opt ≥ 70°C) is facilitated recovery of volatile chemicals from the vapor phase of an active fermenting culture. This process would reduce purification costs and concomitantly alleviate toxicity to the cells by continuously removing solvent fermentation products such as acetone or ethanol, a process we are calling "bio‐reactive distillation."